Considerazioni metodologiche sull’individuazione dei sensi - Andrea Togni (Rivista Internazionale di Filosofia e Psicologia, 2018)
In this paper, I discuss some methodological issues relevant to the debate on the individuation of the sensory modalities. First, I make a distinction between a metaphysical question related to the nature of the senses, and a classificatory question related to their taxonomization. The criteria commonly used to individuate the senses should be able to address both questions. Second, I articulate five grey areas, namely, five groups of problematic cases that authors interested in defending a specific criterion should be able to tackle. The aim of this paper is not to discuss these criteria and grey areas per se, but to clarify some methodological premises that frame the debate under consideration.